Mapping the need for adaptation: assessing drought vulnerability using the livelihood vulnerability index approach in a mid-hill region of Nepal - Mainali, Janardan; Pricope, Narcisa G. (Climate and development, 2019)
For effective development and adaptation interventions in resource-poor regions to take place, it is critical to identify, at the highest spatial scale possible, regions of higher priority based on current needs and vulnerabilities. The index-based assessment of vulnerability to climate change and variability is typically used to identify administrative-level regions of high vulnerability using various socioeconomic and biophysical datasets. One method that combines both approaches at the community level consists of collecting highly resolved socio-economic data and using the livelihood vulnerability index (LVI) to assess population vulnerability to increased climate variability and shocks. We use this mixed-methods approach in mapping climate vulnerability of ten drought-prone villages in the central-east mid-hill region of Nepal. We integrate data from over 900 household surveys and national-level databases and identify spatial patterns in the different components of climate vulnerability. We assess to what extent climatic extremes or people's socioeconomic capacity contribute to vulnerability and may shape development needs at the sub-district scale. We find that the majority of our study area falls in the high vulnerability category with significant spatial variation. In some villages, there are different vulnerability classes in different wards, indicating that even within the lowest administrative units, there is a significant spatial variation in the level of vulnerability. Livelihood strategies, water availability, and topographic components played the most important role in determining overall vulnerability and we measure strong interconnections among different components. The interconnectedness nature of different vulnerability components is creating a self-reinforcing downward spiral of vulnerability that traps local communities in a state of heightened vulnerability. We conclude that adaptation strategies in highly vulnerable regions should include careful consideration of different livelihoods and environmental components, their fine-scale spatial variations, and interconnections.